Screening Potential Citrus Rootstocks for Phytophthora nicotianae Tolerance - Madhurababu Kunta; Sandy Chavez; Zenaida Viloria; Hilda S. del Rio; Madhavi Devanaboina; George Yanev; Jong-Won Park; Eliezer S. Louzada (HortScience, 2020)
Seeds from four citrus rootstocks including sour orange, Bitters-C22 citrandarin, Sarawak pummelo , Rio Red grapefruit, and Sarawak pummelo , Bower mandarin were exposed to high inoculum levels of Phytophthora nicotianae to screen for tolerance. Inoculation of pregerminated seeds (PGIS) and non-PGIS was carried out. The average P. nicotianae propagule counts from the soil samples where these seedlings were raised ranged from 424 to 1361 colony forming units/cm3. The proportion of live to dead plants was recorded at 11 months postinoculation, which showed that Sarawak Bower performed significantly better than other rootstocks. Evaluation of the rootstocks 18 months postinoculation resulted in only one surviving sour orange plant, which suggests potential rootstock resistance.